Deteksi Telur Fasciola sp. Pada Feses Sapi Dengan Metode Sedimentasi - Fitriyah, Izza Nailatul (Maliki Interdisciplinary Journal, 2025)
Fasciolosis is a disease caused by Fasciola sp. parasite infection that commonly affects ruminants, especially cattle. This infection reduces meat and milk productivity and causes economic losses. Transmission occurs through the consumption of feed or water containing metacercariae, so early detection is crucial to prevent the spread. This study aims to identify the presence of Fasciola sp. eggs in cattle feces using the sedimentation method. This study used an experimental approach method on 99 cow feces samples. The examination procedure included dilution, filtration, repeated sedimentation, sediment staining with 1% Methylene blue, and observation using a stereomicroscope. From the examination results, 10 samples (10.1%) were found to be positive for Fasciola sp. eggs with a characteristic brownish-yellow oval shape, while 89 samples (89.9%) were negative and only showed blue sediment. These findings indicate that most livestock are not infected, but the presence of positive cases indicates the potential for transmission in the livestock environment.